2015
DOI: 10.18632/oncotarget.4722
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen related receptor α (ERRα) a promising target for the therapy of adrenocortical carcinoma (ACC)

Abstract: The pathogenesis of the adrenocortical cancer (ACC) involves integration of molecular signals and the interplay of different downstream pathways (i.e. IGFII/IGF1R, β-catenin, Wnt, ESR1). This tumor is characterized by limited therapeutic options and unsuccessful treatments. A useful strategy to develop an effective therapy for ACC is to identify a common downstream target of these multiple pathways. A good candidate could be the transcription factor estrogen-related receptor alpha (ERRα) because of its ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 42 publications
2
36
0
Order By: Relevance
“…In direct support of our hypothesis, TAMR cells showed a significant increase in both mitochondrial mass and mitochondrial membrane potential (Figure 5), as observed by FACS analysis using MitoTracker vital dyes as probes (Deep Red and Orange) [19, 20]. However, this phenotype was strictly dependent on the presence of tamoxifen in the tissue culture media.…”
Section: Resultssupporting
confidence: 78%
“…In direct support of our hypothesis, TAMR cells showed a significant increase in both mitochondrial mass and mitochondrial membrane potential (Figure 5), as observed by FACS analysis using MitoTracker vital dyes as probes (Deep Red and Orange) [19, 20]. However, this phenotype was strictly dependent on the presence of tamoxifen in the tissue culture media.…”
Section: Resultssupporting
confidence: 78%
“…Pellets were re-suspended in 70% ice-cold ethanol for 30 min at 4 • C to perform cell fixation. Then, samples were rinsed twice with PBS and stained using a solution containing 3.8 mM sodium citrate (Sigma-Aldrich, Milan, Italy), 100 µg/mL RNAse (Sigma-Aldrich, Milan, Italy), 50 µg/mL propidium iodide (PI, Sigma-Aldrich, Milan, Italy), and 0.1% Igepal (Sigma-Aldrich, Milan, Italy) in PBS for 1 h at 37 • C. Subsequent cytofluorimetric analysis [34] was achieved by BD FACSJazz™ Cell Sorter (Becton Dickinson, Franklin Lakes, NJ, USA).…”
Section: Cell Cycle Analysismentioning
confidence: 99%
“…Th e changes in these genes expression in cells without IRE1 signaling enzyme function possible contribute in the suppression of glioma cell proliferation and tumor growth, because there are data indicating that the estrogen receptor related factors play an important role in the control of cell proliferation and apoptosis (Cho et al 2010;Lapierre et al 2015;Tiwari et al 2015). It is possible that increased expression of FAM162A, PGRMC2, TRIM16 and SLC39A6 genes as well as decreased expression of ESRRA, and NRIP1 genes (Figure 1) may contribute to the suppression of the proliferation and glioma growth from glioma cells with IRE1 knockdown (Auf et al 2010(Auf et al , 2013Aziz et al 2015;Casaburi et al 2015;Minchenko et al 2015;Zhang et al 2015;Matsushima et al 2016). Th erefore, suppressing of NRIP1, which modulates transcriptional activity of the estrogen receptor, as well as knockdown of a site-specifi c transcription regulator ESRRA/NR3B1 inhibits growth of the cancer cells in vitro and in vivo (Aziz et al 2015;Matsushima et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…ESRRA is widely expressed in a range of tissues and accumulating evidence has supported that the high expression of ERRα correlates with poor prognosis of various human malignancies. However, knockdown of NR3B1 has antitumor eff ect (Casaburi et al 2015;Zhang et al 2015;Matsushima et al 2016). It has been reported that mitochondrial biogenesis is required for the anchorageindependent survival and propagation of stem-like cancer cells and regulated by various transcription factors including ESRRA Wada and Nakatsuka 2016).…”
mentioning
confidence: 99%